Tunnelling the Internet - Akter, Habiba; Phillips, Chris (Journal of Telecommunications and the Digital Economy, 2019)
Despite a considerable increase in Internet capacity, regional congestion is still an issue at certain times of day. Dimensioning the system to provide minimal delay under these transient conditions would be uneconomical. We therefore investigate a scheme that allows end-users to selectively exploit a sequence of mini-tunnels along a path from their origin to a chosen destination. Such tunnels can be advertised centrally through a broker, with the cooperation of the Autonomous System (AS) domain operators, similar to a driver choosing to use a toll road to avoid potential congestion. It is thus a type of loose source routing. The approach avoids the need for inter-operator cooperation, although such cooperation could enable extending tunnels across AS peers. We explore the benefit in delay reduction for a given concentration of tunnels within a portion of the Internet. We show that a relatively small number of tunnels can provide worthwhile improvements in performance. We consider both when tunnels are randomly distributed and when they are provided close to an AS domain of interest, where traffic congestion is more likely. In this latter case, even a relatively small number of tunnels can benefit a reasonable number of users across a large region.